Isolation and Characterization of Pectin from Waste of “Raja Nangka” Banana Peels (Musa acuminata (AAA cv)) - Mardiana Prasetyani Putri; Prima Agusti Lukis; Leny Putri Mawarni (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2020)
Raja nangka banana peel contains pectin (10-21%), lignin (6-12%), and galacturonic acid. Pectin is a D-galacturonic acid polymer which connected with the β-1,4-glycosidic bond. Pectin was benefitted a gel form material and thickener making jam and low-calorie food. Pectin was generated with an isolation process. The purpose of this research was isolated and characterized pectin from raja nangka banana peel waste, and then pectin was obtained characterized for know pectin quality. Pectin isolation was done with the reflux extraction method. Pectin extraction uses chloric acid 1 N solvents. Pectin isolation was done at pH 1,5 temperature 90°C for 80 minutes. The purpose of testing for the function group was known as groups in pectin isolation. The functional group in pectin was got and then characterized with FTIR to show group vibration OH, CH3, C=O, C-H-, and R-O-R, with a wavelength respectively 3.448,366; 2.930,022; 1649,310; 1385,247 and 1146,453. Other than, pectin physical nature was done such as water content (0,061%), ash content (1,994%), equivalent weight (748,29%), methoxyl content (6,90%), galacturonic acid (250,88%) and esterification degree (0,0156%). Pectin characterization was got correct with pectin quality standard based on IPPA (International Pectin Producers Association).